Decision making regarding organ donation from brain dead patients - Alibeigi, Ehsan; Ghorbani , Fariba; Mokhber Dezfuli , Mojtaba; Mohseni, Bardia; Mohseni , Arshia; Cheraghi, Fahimeh; Abdolmohammadi, Yazdan (Researcher Bulletin of Medical Sciences, 2024)
One of the most important obstacles to organ donation is when a family refuses to consent to donate the organs of a brain-dead case. This affects the number of people who die while waiting for an organ transplant. Thus, to increase the number of organs available for transplantation, we need to understand the causes of family refusal. Indeed, there are many reasons why a family refuses to donate organs after the brain dead, including cultural, religious, scientific, social, moral, spiritual, and legal reasons. Therefore, this article reviews and summarizes the significant and influential causes of family refusal among the next keen brain death cases.